Coamplification of Myc/Pvt1 and homozygous deletion of Nlrp1 locus are frequent genetics changes in mouse osteosarcoma. Issue 12 (10th September 2015) - Rao, Pulivarthi H.; Zhao, Shuying; Zhao, Yi‐Jue; Yu, Alexander; Rainusso, Nino; Trucco, Matteo; Allen‐Rhoades, Wendy; Satterfield, Laura; Fuja, Daniel; Borra, Vishnupriya J.; Man, Tsz‐Kwong; Donehower, Lawrence A.; et al.
<x xml:space="preserve">Abstract</x> Osteosarcomas (OSs) are characterized by high levels of genomic instability (GI). To gain insights into the GI and its contribution toward understanding the genetic basis of OS, we characterized 19 primary and 13 metastatic mouse tumors in a genetically engineered novel mouse model of OS by a combination of genomic techniques. Through the bone‐specific deletion of the wild‐type Trp53 locus or activation of a metastatic‐promoting missense R172Hp53 allele, C57BL/6 mice developed either localized or metastatic OS. Subsequent tumors were isolated and primary cultures created from primary bone and/or distal metastatic lesions, for example, lung and liver. These tumors exhibited high levels of GI with complex chromosomal rearrangements, amplifications, and deletions comparable to human OS. The combined genomic approaches identified frequent amplification of chromosome 15D1 and loss of 11B4 by CGH and/or SKY. Both 15D1 and 11B4 have homology with frequently altered chromosomal bands 8q24 and 17p13 in human OS, respectively. Subsequent array CGH, FISH, and qRT‐PCR analysis identified coamplification and overexpression of Myc/Pvt1 transcripts from the 15D1 amplicon and loss and decreased expression of the Nlrp1b from 11B4. The Nlrp1 gene is the key mediator of apoptosis and interacts strongly with caspase 2. © 2015 Wiley Periodicals, Inc.